Energy research in Nigeria: A bibliometric analysis - H.B. Adedayo; S.A. Adio; B.O. Oboirien (Energy Strategy Reviews, 2021)
The scant supply of energy in Nigeria in relation to its energy demand has triggered interest in the scientific investigation of various energy research. This study reports on the bibliometric analysis of energy publications from Nigerian researchers from 1974 to 2019 (45 years) from the Elsevier Scopus database. The analysis includes publication types, languages of publication, institutions of authors and collaborators. Based on the analysis, the number of publications has increased in the 45 years period. With significant changes being from the period 2006–2015 by an average of 113 publications per year, to an average of 326 publications per year from 2016 to 2019. The contributions of institutional energy publications by region showed that the South-Western States region had the highest number of publications. A global map showing energy collaboration at international level Nigerian-authors mainly co-author energy publications with South Africa, Malaysia, the United States and the United Kingdom institutions. The publications are mainly in solar energy, wind energy and biomass energy and surprisely less in gas and hydro energy which are the main sources of electricity generation in Nigeria.